2018
DOI: 10.1016/j.cemconcomp.2017.10.010
|View full text |Cite
|
Sign up to set email alerts
|

ASR expansions in concrete under triaxial confinement

Abstract: It is well known that the Alkali-Silica Reaction (ASR) expansion in concrete is influenced by the stress state of the material. However, the extent and nature of this influence is not completely understood due to the scarcity of experimental investigation under triaxial stress states. This paper presents experimental ASR expansion curves obtained from cubical concrete specimens subjected to three different triaxial stress states, by means of a new testing machine especially designed for this purpose. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 8 publications
0
30
0
Order By: Relevance
“…In this proposed model, the heat-diffusion analysis is decoupled from mechanical analysis, and the output from preliminary thermal analysis is used as a predefined field for the next analysis including ASR and mechanical damage. The model is validated at the material scale on the basis of the recently published paper on experimental modelling of ASR considering the triaxial stress state [16]. At structural level, a finite element model is constructed for a gravity dam suffering from ASR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this proposed model, the heat-diffusion analysis is decoupled from mechanical analysis, and the output from preliminary thermal analysis is used as a predefined field for the next analysis including ASR and mechanical damage. The model is validated at the material scale on the basis of the recently published paper on experimental modelling of ASR considering the triaxial stress state [16]. At structural level, a finite element model is constructed for a gravity dam suffering from ASR.…”
Section: Discussionmentioning
confidence: 99%
“…However, the results from Larive [15] indicate that such phenomena do not occur in ASR, at least in the range of stresses encountered in the field. To the contrary, in a recent experimental research by Liaudat et al [16], it has been shown that a 3D state of permanent stress equal to -9.7 MPa can hinder the volumetric ASR strains. Mechanical loads also affect the fracture processes in the material, and therefore the expansion as it is, in ASR, may be strongly coupled with internal damage [17].…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…For such multiaxial loading, the experiments in the literature show that the measured volumetric expansion decreases [56], [57]. In the model, as long as the cracking criterion (Equation 15) is not reached, the volume of cracking, , stays equal to zero and the pressure increases (Equation (1)).…”
Section: Pressure Evolution During Diffuse Crackingmentioning
confidence: 99%
“…Under anisotropic mechanical loading, expansions are anisotropic [36], [37], [43], [54]- [57]. For different natures of new phases (alkali silica gels or ettringite), a difference of 1 MPa in stress compared to the mean stress in the material is sufficient to cause anisotropic expansion [36], [38], [54], [58].…”
Section: Anisotropy Of Cracking Due To Macroscopic Stress Statementioning
confidence: 99%